Pengaruh Komunikasi terhadap Kinerja Komunitas Fotografi Medan - Ritonga, Elfi Yanti; Sugiarto, Samudra; Nanda Amelia, Ramadhani; Mutahar, Lola Fahira; Maisarah, Maisarah; Muridayani, Muridayani (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
People who share the same interests can gather in a community. People will receive knowledge from one another and experiences that promote talents or abilities related to interests through the community. There are several communities in Medan City. One of them is the Medan Photography Community. Usually, Communities in other areas have different communities, such as the Food Photography Community, such as the Event Photography Community, such as the Huntung Photography Community, and others. But the Photography Community in Medan covers it all. On Tuesday, May 22, 2011, the Medan City Photography Lovers Community was established with the aim of being a forum for the aspirations of local photographers in the city of Medan and its surroundings. Regardless of the type of camera, Canon, Nikon, Yashica, Pentax, Ricoh, Vivitar, Fujica, Lomo, Polaroid, etc. No problem, those who like photography are welcome to join. In this community, it is hoped that fellow members can share knowledge with each other. This research uses descriptive quantitative research. The data is divided into two categories, namely primary and secondary. Primary data comes from observations, interviews, and documentation, while the second data comes from captions posted by the Medan Photography Community Facebook account. Data analysis techniques include data editing, collection, presentation, and analysis of conclusions. Solid membership and administration, open to anyone who wants to learn and have insight and have a social spirit towards those who need help, are aspects that support the community's reputation. The large number of new members joining the community made it more difficult for administrators to monitor member communications, which resulted in a lot of discussion outside the realm of photography. Currently the need for photographers is increasing, as evidenced by the rise of the photography community and the number of photography lovers. Photography has evolved from a certainty to a viable career choice. The simplicity of today's cameras allows everyone to capture important events, but if the results don't match expectations, the skills of a photographer are needed. Choosing a photographer is simple because of the many choices and various factors. Therefore, in this study, a decision support system was developed to help simplify services for photographers who meet the requirements that have been set.